Case report: Intraoperative reversal of flow through an atrial septal defect presenting as hypoxemia during off-pump coronary artery bypass grafting - Zhao, Yun; Mi, Chaorui; Xie, Juan; Li, Hui (Frontiers in Cardiovascular Medicine, 2023)
The co-existence of atrial septal defect and coronary artery disease in a patient is rare in clinical practice. In the combined surgery of off-pump coronary artery bypass grafting and atrial septal defect closure, the unusual cardiac positions may affect the direction of blood shunting between the atriums, leading to more complex hemodynamic changes. Here, we report a case of a 67-year-old female who underwent refractory hypoxemia related to heart position in such a combined operation.